(untitled) - Font, C.=700 1 Curbelo, I.; Fernandez, J.; Valdes, S.; Pereira, D.
(Es, En)
Ilus., 14 ref.
Deteccion de particulas baciliformes en los hibridos de platano FHIA-21 en Cuba
Keywords: PLATANO; VIROSIS; DIAGNOSTICO; CUBA; BSV; FHIA-21